An Aluminum(III)-Catalyzed Thioamide–Aldehyde–Styrene Condensation: Direct Synthesis of Allylic Thioamide Derivatives - Xu, Bin; Zhong, Xue; Wang, Xi-Cun; Quan, Zheng-Jun (Synlett, 2016)
An aluminum(III) triflate catalyzed three-component synthesis of allylic thioamide derivatives by condensation of a thioamide, paraformaldehyde and a styrene is reported.
Keywords: thioamides; paraformaldehyde; styrenes; allyl thioamides; multicomponent reactions; condensation